Novel temperature measurement and profiling system for bioclimatic building material / Mohd Nasir Taib … [et al.] - Taib, Mohd Nasir; Zain Ahmed, Azni; Mohd Shah Baki, Shahrizam; Md Zain, Zainazlan (2003)
Energy in building has a lot of purpose. One of it is to condition the space for thermal comfort. For hot and humid country like Malaysia, the excess heat that is transferred into a building and increases the internal temperature causes much discomfort. In order to maintain the thermal comfort, this excess heat must be extracted out from the building space. Material for the building envelope plays a very important role to influence the rate of heat transfer. Understanding the thermal behavior will enable engineer to select suitable materials and to design the optimum dimension for building walls from energy efficient perspective. This research project is able to display the thermal behavior of building material under the influence of solar radiation. The temperature profile will display the thermal behavior of building material.